The Influence of Ownership Structure and Liquidity on Dividend Policy in ASEAN Banking - Achmad Gibran Fachraesy; Mawjihan Tsakilla; Farah Margaretha Leon (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research seeks to explore and critically assess the influence of ownership structure and liquidity on banking dividend policies in Indonesia, Malaysia, and Thailand. The sample consists of 25 banking companies total of 100 data points were gathered through a purposive sampling approach. The research utilizes secondary data, specifically banking annual reports from the 2020–2023 period, sourced from the Indonesia Stock Exchange, Malaysia Stock Exchange, and Thailand Stock Exchange. The analytical framework applied is multiple linear regression. The findings reveal that foreign ownership, bank performance, and leverage exert a negative influence on dividend policy, whereas institutional ownership, liquidity, and bank age do not demonstrate a statistically significant impact on dividend policy, as reflected in dividend yield and dividend payout ratio . The findings also indicate that institutional ownership negatively affects dividend policy when measured by dividend yield. This research is expected to benefit financial managers and investors in decision-making. For financial managers, insights into the influence of ownership structure on dividend policy can assist in designing financial strategies, managing liquidity, and determining dividend distribution. Meanwhile, for investors, this information serves as a basis for making more informed investment decisions.